School Principals’ Strategic Planning Competences And Their Influence On Academic Performance In Public Secondary Schools In Makueni County, Kenya - Sila, Killian Muendo; Njihia, Mukirae (Journal Integration of Social Studies and Business Development, 2025)
This study investigates the impact of strategic planning competencies on the academic performance of public secondary schools in Makueni County, Kenya. Specifically, it examines how principals' competencies in human resource planning, technology integration, school culture alignment, and strategic direction-setting influence academic outcomes. Grounded in the contingency theory of leadership, the study employs a descriptive research design. The target population included 385 public secondary schools in Makueni County, with principals and teachers as key respondents. A 10% sampling threshold was applied, resulting in a sample of 39 schools. School principals were purposively selected, while 368 teachers were randomly sampled using a structured formula. Data were collected via questionnaires for teachers and interview guides for principals and analyzed using both qualitative and quantitative methods. The findings indicate that human capital development is a critical strategic competency among school principals that significantly enhances academic performance. Furthermore, principals' ability to leverage ICT positively affected academic outcomes. School culture alignment emerged as another essential competency, impacting the schools' overall performance. Additionally, the ability of school principals to set a clear strategic direction was found to play a significant role in achieving academic success. The study concludes that poor academic performance in Makueni County’s secondary schools is closely associated with deficiencies in principals' strategic planning competencies, particularly in areas such as human capital development, ICT integration, strategic direction-setting, and school culture alignment. The study recommends that school principals enhance their strategic planning skills to improve academic performance.